RANCANG BANGUN PROTOTIPE MESIN PLUTO (PLASTIC-TO-OIL) - Nurjanah Nurjanah; Dawi Yanti; Adelia Rohani; M Saleh; Ranjiv Maulana; Ain Sahara; Dhaffa Bhanu Pangestu; Mohammad Lutfi (Sekolah Tinggi Teknologi MIGAS, 2023)
The increase in plastic waste demands acceleration of waste recycling technology. The purpose of this research is to make a prototype machine to process plastic waste into liquid fuel using the pyrolysis method called the Pluto (plastic to oil) engine. This machine can accommodate plastic waste with a maximum weight of about 3 Kg with a condensate tube that can accommodate a maximum volume of about 3 L of liquid fuel. Experimental results reveal that the heating process for 2 hours produces 250 mL of liquid fuel.